Desiminasi Ideologi Jihadi Kaos Islam Anak-Anak Pada Distro Rafa Muslim Fashion Di Surakarta - Saputra, Eko; Ardi, Ardiansyah (Journal of Community Development and Disaster Management, 2025)
This article, study examines the dissemination of jihadist ideology among in Surakarta Muslim children through to clothing/fashion. This research takes the case study of Rafa Muslim Fashion (RMF). The RMF was chosen as the object of research because in Surakarta the massive desimination of jihad ideology through dakwa t-shirts. By taking, the RMF kidz jihadi children's shirts, this study answers the question of why jihadi actors spread the ideology of radicalism through Islamic t-shirts? What is the pattern of radicalism promoted by RMF in the Islamic Jihadi shirt? How did the children respond to the Muslim Jihadi kidz t-shirts? To answer this research, the author conducted field research at the RMF distribution in Surakarta. The author argues that Muslim children in Indonesia, especially, Ngeruki, Surakarta, are exposed to the ideology of jihad to fashion dakwa t-shirt is because of the introduction of heroic figures through Islamic t-shirts. Koas Islam is used as a medium for desimination jihadi ideology alternative by actors jihadi. Through dakwa t-shirts that are designed in a trendy, stylish and modern way, Muslim children are attracted to jihadi t-shirts.